Experimental measurements of vapor-liquid equilibria at low pressure: Systems containing alcohols, esters and organic acids - Navarro Espinosa, Iván R. (2010)
In this work the vapor-liquid equilibria for nine binary mixtures (methanol + acetic acid, methanol + methyl acetate, methanol + water, methyl acetate + acetic acid, water + acetic acid, ethyl acetate + acetic acid, ethanol + acetic acid, ethanol + ethyl acetate and ethanol + water) at subatmospherical pressure (580 mmHg) is presented. Peng-Robinson Stryjek-Vera equation of state coupled with the Wong-Sandler mixing rules were used for predicting phase equilibria of these mixtures. The measurements were developed using an apparatus with recirculation that can also be employed for liquid-vapor equilibrium with chemical reaction. Crown Copyright © 2009.